Region Based Huffman (RBH) Compression Technique with code interchange - Nandi, Utpal; Mandal, Jyotsna Kumar (Malaysian Journal of Computer Science, 2010)
the performance of Huffman coding. The proposed paper is based on the new technique region based Huffman to increase the performance of the Huffman coding. The proposed technique divides the input file into a number of regions. Huffman codes are obtained for entire file. For each region, the code between the maximum frequency element of that region and maximum frequency element of entire file are interchanged and the symbols of that region are compressed. This is repeated for each region. Then a small variation of the technique is proposed where instead of interchanging the codes of elements, selection of number of region is done by a proposed algorithm. This modified technique eliminates some limitations of previous proposed technique. Comparisons are made among these two variants with classical Huffman technique.